2019
DOI: 10.18823/asiatefl.2019.16.4.5.1135
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Writing Assessment Literacy and Classroom Practices of Thai University Instructors

Abstract: This study aims to explore Thai university writing instructors' knowledge of writing assessment and their perceptions of different assessment practices. Having a good understanding of assessment principles is important because it helps teachers choose and develop appropriate assessment tools to measure students' abilities. Two major research questions are how much Thai university instructors know about writing assessment and whether they received any formal training in writing assessment before they started te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…Similar to many studies in the literature (Ataie-Tabar et al, 2019;Crusan et al, 2016;Mellati & Khademi, 2018;Ricky, 2020;Tayyebi et al, 2022;Tayyebi & Moradi Abbasabadi, 2020;Thirakunkovit, 2019), findings of the present study also revealed that although teachers had a positive attitude toward writing assessment and considered themselves as assessment literate, their level of assessment literacy was not reflected in their practice, particularly when it came to rubric use. This contradictory finding can be explained Scoring of writing is subjective (Q19) 1.7 41.5 9.3 37.3 3.4 3.1 1.1…”
Section: Discussionsupporting
confidence: 87%
“…Similar to many studies in the literature (Ataie-Tabar et al, 2019;Crusan et al, 2016;Mellati & Khademi, 2018;Ricky, 2020;Tayyebi et al, 2022;Tayyebi & Moradi Abbasabadi, 2020;Thirakunkovit, 2019), findings of the present study also revealed that although teachers had a positive attitude toward writing assessment and considered themselves as assessment literate, their level of assessment literacy was not reflected in their practice, particularly when it came to rubric use. This contradictory finding can be explained Scoring of writing is subjective (Q19) 1.7 41.5 9.3 37.3 3.4 3.1 1.1…”
Section: Discussionsupporting
confidence: 87%
“…The teachers answer the items about their teaching and perform writing assessments in their classroom in more detail and depth because there are no limited answers for the respondent. Open-ended questionnaire adopted and adapted from Thirakunkovit (2019).…”
Section: Methodsmentioning
confidence: 99%
“…According to Thirakunkovit (2019) writing assessment literacy refers to the range of expertise that teachers need to accurately evaluate and rank their students' work. List of important literacy assessments for writers: knowledge of writing standards, understanding of assessment types, rubric development, analyzing and interpreting writing samples, feedback and grading, assessment bias awareness, data analysis.…”
Section: Writing Assessment Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…A standardized evaluation instrument using a holistic score system has been created to measure learners' cognitive abilities that cannot be measured by objective tests. Thirakunkovit (2019) reported that the evaluation results relate current practices to successful writing and subsequent discussion of how to change the writing curriculum. Formative testing has culminated in students developing their writing abilities for academic purposes.…”
Section: The Quality Of the Task-based Materials Design To Improve Ewamentioning
confidence: 99%